2016
DOI: 10.1016/j.ihj.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inferior vena cava diameter by echocardiography in normal Indian population: A prospective observational study

Abstract: Our findings corroborate the correlations between height, weight and BMI with IVC diameter. Future studies could be focused to bring about a steadfast formula for calculating IVC diameter based on demographic parameters of an individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 25 publications
(24 reference statements)
3
33
0
3
Order By: Relevance
“…We determined a pre‐donation IVCmax of 17.4 ± 3.1 mm and IVCmin of 10.1 ± 2.7 in our healthy population sample. Patil et al studied IVC diameter in 4126 volunteers from an healthy population and reported an IVCmax of 16.9 ± 3.7 and IVC min diameter of 10.4 ± 2.2, comparable with our own results . We detected a 2.2 mm decrease in IVCmax after blood donation in our BD group.…”
Section: Discussionsupporting
confidence: 91%
“…We determined a pre‐donation IVCmax of 17.4 ± 3.1 mm and IVCmin of 10.1 ± 2.7 in our healthy population sample. Patil et al studied IVC diameter in 4126 volunteers from an healthy population and reported an IVCmax of 16.9 ± 3.7 and IVC min diameter of 10.4 ± 2.2, comparable with our own results . We detected a 2.2 mm decrease in IVCmax after blood donation in our BD group.…”
Section: Discussionsupporting
confidence: 91%
“…29,71 Although US assessment of IVC is generally believed to be very effective in estimating the intravascular volume and have a crucial influence, a question remains about the accuracy for new patients accepted at emergency care units 72 because the size and dynamics of IVC vary significantly from patient to patient. 73 A high accuracy is generally expected by measuring IVC repeatedly at every visit, which makes it possible to detect an abnormal IVC in contrast to a normal IVC, 29 and by sharing data recorded by US, e.g., phUS, and various clinical information with other key personnel of the medical care team, especially physicians and US experts, via a network or the Internet. This way, a consistent level of care quality will be ensured also for newly arriving patients.…”
Section: Us For Clinical Decision Making In Home Medical Carementioning
confidence: 99%
“…For assessing intravascular volume status, IVC measurements using ultrasonography (USG) is a reliable noninvasive technique. Central venous pressure (CVP) has a positive correlation with IVC size and negative correlation with IVC collapsibility index (IVCCI) . IVCCI can be a better indicator than IVC diameter, as it is a dynamic parameter which takes the variation of diameter over the respiratory cycle into account .…”
Section: Introductionmentioning
confidence: 99%
“…Central venous pressure (CVP) has a positive correlation with IVC size and negative correlation with IVC collapsibility index (IVCCI). 17,18 IVCCI can be a better indicator than IVC diameter, as it is a dynamic parameter which takes the variation of diameter over the respiratory cycle into account. 19 IVC diameter may be underestimated due to the "cylinder tangent effect" if the US beam travels through the vessel longitudinally in an offcentered plane.…”
Section: Introductionmentioning
confidence: 99%